1987
DOI: 10.1159/000138279
|View full text |Cite
|
Sign up to set email alerts
|

Specificity of the Substituted Benzimidazole B 823-08: A Prodrug for Gastric Proton Pump Inhibition

Abstract: Substituted benzimidazoles are potent inhibitors of the parietal cell proton pump, the H+/K+-ATPase. One member of this group, the sulfide B 823-08 (2-[(4-methoxy-3-methyl-2-pyridylmethyl)-thio]-5-trifluoromethyl-(lH)-benzimidazole) inhibits gastric acid secretion in various in vivo models, but fails to affect acid secretion in the isolated, lumen perfused mouse stomach. In contrast, the corresponding sulfoxide (B 823-10) is active under both in vivo and in vitro conditions. Since the sul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1989
1989
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Interestingly, these findings were more pronounced in female animals, suggesting that factors related to sex modify the response of gastric endocrine cells to drug-induced achlorhydria at least in animals. Recently, it has been demonstrated that this reciprocal behaviour is reflected by respective changes in antral gastrin and so matostatin mRNA supporting the hypothe sis that gastric pH influences release and syn thesis of gastrin and somatostatin [24], Rep resentative examples for the morphological events are presented in figures 3-6, using BY 308, a prodrug metabolized within the body into the active drug [25], for long-term toxic ity studies in female rats ( fig. 3, 4) and in female dogs ( fig.…”
Section: Studies In Animalsmentioning
confidence: 63%
“…Interestingly, these findings were more pronounced in female animals, suggesting that factors related to sex modify the response of gastric endocrine cells to drug-induced achlorhydria at least in animals. Recently, it has been demonstrated that this reciprocal behaviour is reflected by respective changes in antral gastrin and so matostatin mRNA supporting the hypothe sis that gastric pH influences release and syn thesis of gastrin and somatostatin [24], Rep resentative examples for the morphological events are presented in figures 3-6, using BY 308, a prodrug metabolized within the body into the active drug [25], for long-term toxic ity studies in female rats ( fig. 3, 4) and in female dogs ( fig.…”
Section: Studies In Animalsmentioning
confidence: 63%
“…Because of the high effective concentration, the electrophilicity of the reactive group can be drastically decreased to provide a degree of selectivity for labeling one site on a particular protein in competition with non‐selective labeling of other proteins or small molecules that contain nucleophiles with similar reactivity. A number of other complementary strategies have been applied to increase the selectivity of affinity labels in proteomic mixtures, cells, or organisms, with three listed here as examples: 1) the proton pump inhibitor omeprazole uses a prodrug approach in which the reactive electrophile that acts as an affinity label is only generated near the site of action; 2) the opposite “soft drug” approach was applied to acrylamide‐based modifiers by designing them to be rapidly metabolized into unreactive compounds when not bound to their targeted site; 3) a third strategy increases the reversibility of covalent bond formation in order to decrease off‐target labeling, for which there is little noncovalent affinity to drive the equilibrium forward…”
Section: Introductionmentioning
confidence: 99%
“…17 Reaction of 1 with substitutedphenacyl bromide is reported 18 to yield 2-(2-4-substitutedphenyl)-2-oxo-ethylthio)-3-substituted-quinazolin-4(3H)-ones. Literature studies indicate different methods 19 for the preparation of 4-oxo-3, 4-dihydroquinazoline-2-yl-sulfanyl)-acetic acid (2). N-Chloroacetylanthranilic acid ethyl ester is reported 20 to react with potassium thiocyanate giving 2.…”
Section: Synthesis Of Novel 2-(4-oxo-3 4-dihydroquinazolin-2-ylsulfimentioning
confidence: 99%